DIPG-05. A RATIONAL COMBINATION STRATEGY TARGETING ATM KINASE IN PEDIATRIC HIGH-GRADE GLIOMA. (23rd April 2019) - Xie, Jia; He, Chen; Bianski, Brandon; Twarog, Nathaniel; Baker, Suzanne; Shelat, Anang; Tinkle, Christopher
Abstract: Radiation therapy (RT) is a standard component of postoperative management of children with malignant gliomas and the definitive therapy for patients with inoperable high-grade glioma (HGG), yet the duration of benefit is generally measured in months to several years. Therefore, it is important to identify novel systemic therapy agents that enhance the therapeutic efficacy of standard of care RT. We screened a custom library of 24 FDA approved drugs and late stage clinical candidates with reported radiosensitizing activity and central nervous system (CNS) penetration, including direct inducers of DNA damage and inhibitors of the DNA damage response, in combination with a dose-response of ionizing radiation (IR) in three diffuse intrinsic pontine glioma (DIPG) cell lines using the CellTiter-Glo assay, clonogenic assay, and/or live cell confluence assay. DNA damage was interrogated by measuring the formation of γ-H2AX foci and micronuclei using immunoflourescence microscopy. DNA repair efficiency was measured using the EJ-DR reporter system. Cellular senescence was quantified by senescence-associated β-galactosidase staining. The CNS penetrant ATM inhibitor, AZD1390, emerged as the best potentiator of IR across all three DIPG models. Preliminary results indicated that AZD1390 inhibited the formation of γ-H2AX foci immediately after the application of IR, but led to persistence of foci at longer timepoints. Drug treatment enhanced IR-induced cellular senescence and increased mutagenic non-homologous end joining (mNHEJ). Furthermore, the PARP inhibitor olaparib and the topoisomerase I inhibitor topotecan strongly potentiated with AZD1390 independently of IR. Taken together, our work provides strong rationale for the in vivo evaluation of combination therapy incorporating ATM inhibition with conventional DNA damaging therapy in pediatric (p)HGG xenograft models. To this end, ongoing work includes in vivo RT dose-response and CNS pharmacodynamics following AZD1390 treatment of pHGG xenografts.